(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
With occurrence of any financial crises, regardless at global or regional levels such as the great economic crises during 1929 – 1933 and the Asian financial crises at the end of twentieth century as well as the current global financial crises that started during second half 2008, we acknowledge that there are some critics loudly articulated accusing accountants and auditors for disparences, and they are numerical partner of financial manipulation as well as corrupted administrators with the company’s administrators that they are difficulty. At this point, many suggestions and recommendation for upgrading the accounting system has been made. We opinion that the above critics mentioned to problems in accounting thought, despite of numerous stages that accounting theorize went through until our present time except we facing problems thinking can described that critical weakness belief of accounting reporting, there for usually the global financial crises places problems under microscope and push us to more effort in order to raising engine accounting thought so raising accounting practices controlling with scientific origin. The present paper focuses on problems that associated with global financial crises, where we of opinion and we are still at the beginning of the new millennium that the big challenge of contemporary accounting thought lay in solving these problems.